The Distribution and Evolution of Physical Neighborhood Problems during the Great Recession. (13th September 2013) - Allen, Ryan
Abstract : While the Great Recession had clear effects on economic growth, unemployment, and household wealth and earnings in the United States, it also likely affected the quality of neighborhoods. Situated in the literature on locational attainment and economic shocks, this research considers how a national economic crisis affects physical neighborhood problems and existing disparities between minority and white households in experiencing these problems (e.g., street disrepair, trash, abandoned buildings, window bars). Results indicate that neighborhood problems increased between 2005 and 2009 and large and persistent disparities existed between some minority groups and white non‐Hispanics in experiencing these problems, even after controlling for potentially confounding factors. However, there is little support for the idea that disparities between minorities and white non‐Hispanics in experiencing neighborhood problems increased during this time. These research findings suggest that large and pervasive shocks, such as an economic recession, can influence locational attainment by changing neighborhood quality in absolute terms but may not affect the relative hierarchy of place. La Distribución y Evolución de los Problemas Físicos Barriales durante la Gran Recesión